Antifungal potential of Melaleuca alternifolia against fungal pathogen Fusarium oxysporum f. sp. cubense Tropical Race 4 - Paramalingam, Pavitra; Baharum, Nadiya Akmal; Abdullah, Janna Ong; Hong, Jeum Kyu; Saidi, Noor Baity (Multidisciplinary Digital Publishing Institute, 2023)
Fusarium wilt of bananas caused by Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4) poses the most serious threat to banana production globally. The disease has been managed using chemical fungicides, yet the control levels are still unsatisfactory. This study investigated the antifungal activities of tea tree (Melaleuca alternifolia) essential oil (TTO) and hydrosol (TTH) against Foc TR4 and their bioactive components. The potential of TTO and TTH in inhibiting the growth of Foc TR4 was evaluated in vitro using agar well diffusion and spore germination assays. Compared to the chemical fungicide, TTO effectively suppressed the mycelial growth of Foc TR4 at 69%. Both the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of TTO and TTH were established at 0.2 µg/µL and 50% v/v, respectively, suggesting the fungicidal nature of the plant extracts. The disease control efficacies were also demonstrated by a (p ≤ 0.05) delayed Fusarium wilt symptom development in the susceptible banana plants with reduced LSI dan RDI scores from 70% to around 20–30%. A GC/MS analysis of TTO identified terpinen-4-ol, eucalyptol, and α-terpineol as the major components. In contrast, an LC/MS analysis of TTH identified different compounds, including dihydro-jasmonic acid and methyl ester. Our findings indicate the potential of tea tree extracts as natural alternatives to chemical fungicides to control Foc TR4.